Exploring client satisfaction and determinants of family planning services at public health facilities in Debre Tabor town, Northwest Ethiopia: a mixed-method study - Asefa, Tseganesh; Tesfaye, Winta; Bitew, Gedamnesh; Endale, Hiwot Tezera (Frontiers in Reproductive Health, 2025)
IntroductionClient satisfaction is a crucial indicator of family planning service utilization, and understanding these insights is essential for designing responsive, client-centered interventions to address barriers to contraceptive use. This study aimed to explore client satisfaction and determinants of family planning services in public health facilities in Debre Tabor town, northwest Ethiopia.MethodsA convergent parallel mixed-methods design, incorporating both quantitative (facility-based cross-sectional) and qualitative (phenomenological) study approaches, was conducted at public health facilities in Debre Tabor town from April 15 to May 29, 2024. Data were collected using an interviewer-administered questionnaire following a multi-stage stratified random sampling technique. Simultaneously, qualitative data were collected from purposefully selected individuals using an in-depth interview guide. The study used EpiData version 4.6 for data input and SPSS version 25 for logistic regression analysis, using a p-value < 0.05 as the cutoff point. After an in-depth interview, the record and field notes were transcribed, translated, and analyzed using a thematic analysis technique.ResultOut of 379 participants, 62.5% of clients were satisfied with the family planning services. Factors significantly associated with clients' satisfaction were urban residents (AOR = 1.68, p = 0.022), government employees (AOR = 0.40, p = 0.020), shorter waiting times (AOR = 2.93, p = 0.039), method counseling (AOR = 2.32, p = 0.005), and receiving the preferred method (AOR = 2.59, p = 0.024). From the in-depth interview of 15 participants, two themes emerged: “limited provider-client counseling interaction,” with subthemes of “cultural sensitivity gaps,” “misconceptions,” and “fear of ineffectiveness,” and “pathways to satisfaction,” with subthemes of “dignified care” and “accessibility.”Conclusion and recommendationsThe study found moderate client satisfaction with family planning services in public health facilities, with significant disparities in residence, occupation, waiting time, method counseling, and preferred methods. Clients reported a lack of cultural sensitivity, misconceptions, and a lack of involvement in decision-making. To improve satisfaction, health facilities should strengthen client-centered counseling, address cultural misconceptions, and provide flexible service hours and training for providers.